The link between the layperson’s dream interpretations and psychological wellbeing: a case study of the African Apostolic church, Senga branch. - Simunyu, Clement Nyasha (Midlands State University, 2017)
The beliefs about dreams lay people hold, in most cases, are irrational and not true. The study aimed at bringing out that there is a strong relationship between common dream interpretations and diminished Psychological well-being. Aaron Beck and Albert Ellis in their Cognitive Behavioural therapy, argued that, emotional problems such as Anxiety, depression, and stress are a result, not of the actual event, but of one’s beliefs and thoughts about the event. In the same way, the beliefs and thoughts people have of their dreams may affect them emotionally. The research was prompted by the shocking fact of how nightmares are positively correlated with emotional problems such as anxiety and depression, and also the fact that, the brain cannot distinguish the difference between real events and dreams/visions. The research is a phenomenological, and qualitative in nature since detailed explanations where required. A nonprobabilistic sampling technic known as extreme sampling, was used to select The African Apostolic Church, Senga branch, as the targeted population. A snow-ball technic was then applied from which fifteen respondents where used a sample. In-depth interviews were conducted thoroughly on the sample. The data was analysed thematically as per the research questions. About 15 dreams where common amongst the respondents, and their interpretations where based on generally 5 dream interpretation principles which where culturally and religiously derived. Of the 15 reported dreams, 12 dreams had very much negative emotional effects on the dreamers and where associated with 5 emotional problems namely anxiety, depression, stress, paranoia, neurosis and paranoid thinking. Thus, it became justified for the researcher to assume that irrational dream interpretations can affect the psychological wellbeing of the layperson.